Challenger Deep - Shusterman, Neal; Shusterman, Brendan (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2015)
Caden Bosch is on a galleon thats headed for the deepest point on Earth: Challenger Deep, the southern part of the Marianas Trench. Caden Bosch is a brilliant high school student whose friends are starting to notice his odd behavior. Caden Bosch is designated the ships artist in residence to document the journey with images. Caden Bosch pretends to join the school track team but spends his days walking for miles, absorbed by the thoughts in his head. Caden Bosch is split between his allegiance to the captain and the allure of mutiny. Caden Bosch is torn. Caden Bosch is dealing with schizophrenia... and as fantasy and paranoia begin to take over, his parents have only one choice left.
Keywords: Schizophrenia in adolescence -- Juvenile fiction; Teenage artists -- Juvenile fiction; Metaphor -- Juvenile fiction; Ocean travel -- Juvenile fiction